Low back pain associates with altered activity of the cerebral cortex prior to arm movements that require postural adjustment - Jacobs, Jesse V. (2010)
OBJECTIVE: To determine whether low back pain (LBP) associates with altered postural stabilization and concomitant changes in cerebrocortical motor physiology. METHODS: Ten participants with LBP and 10 participants without LBP performed self-initiated, voluntary arm raises. Electromyographic onset latencies of the bilateral internal oblique and erector spinae muscles were analyzed relative to that of the deltoid muscle as measures of anticipatory postural adjustments (APAs). Amplitudes of alpha event-related desynchronization (ERD) and of Bereitschaftspotentials (BP) were calculated from scalp electroencephalography as measures of cerebrocortical motor physiology. RESULTS: The APA was first evident in the trunk muscles contralateral to the arm raise for both groups. Significant alpha ERD was evident bilaterally at the central and parietal electrodes for participants with LBP but only at the electrodes contralateral and midline to the arm raise for those without LBP. The BP amplitudes negatively correlated with APA onset latencies for participants with (but not for those without) LBP. CONCLUSIONS: Cerebrocortical activity becomes altered prior to arm movements requiring APAs for individuals with chronic LBP. SIGNIFICANCE: These results support a theoretical model that altered central motor neurophysiology associates with LBP, thereby implying that rehabilitation strategies should address these neuromotor impairments.